2013
DOI: 10.1016/j.apal.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Uniformly defining valuation rings in Henselian valued fields with finite or pseudo-finite residue fields

Abstract: We give a definition, in the ring language, of Z p inside Q p and of F p [[t]] inside F p ((t)), which works uniformly for all p and all finite field extensions of these fields, and in many other Henselian valued fields as well. The formula can be taken existential-universal in the ring language, and in fact existential in a modification of the language of Macintyre. Furthermore, we show the negative result that in the language of rings there does not exist a uniform definition by an existential formula and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 6 publications
0
48
0
Order By: Relevance
“…. , in K for any p-henselian valued field (K, v) with discrete p-regular value group satisfying one of the three conditions (1)- (3).…”
Section: Value Group Z In the Ring Languagementioning
confidence: 99%
See 1 more Smart Citation
“…. , in K for any p-henselian valued field (K, v) with discrete p-regular value group satisfying one of the three conditions (1)- (3).…”
Section: Value Group Z In the Ring Languagementioning
confidence: 99%
“…[17]. In this language, the following definition has recently been obtained in [3,Theorem 3] using results from the model theory of pseudo-finite fields. Theorem 1.1 (Cluckers-Derakhshan-Leenknegt-Macintyre).…”
Section: Introductionmentioning
confidence: 99%
“…The special case where K is a finite extension of Q p was proven by Cluckers, Derakhshan, Leenknegt, and Macintyre in [5,Theorem 6]. §3.…”
Section: Theorem 12 For Every > 0 There Exists An ∃-∅-Formula ϕ Andmentioning
confidence: 99%
“…For details the reader may consult [5,Theorem 4], where it is shown that no ∃-∅-formula can define the valuation ring uniformly for all finite extensions of a fixed henselian valued field K.…”
Section: Corollary 36 Let K Be a Henselian Valued Field With Valuatmentioning
confidence: 99%
See 1 more Smart Citation